2017
DOI: 10.18671/scifor.v45n114.16
|View full text |Cite
|
Sign up to set email alerts
|

Rust resistance and mating system in Eucalyptus grandis Hill ex Maiden progenies

Abstract: ResumoPopulações de Eucalyptus grandis foram introduzidas no Brasil a partir de Queensland e New South Wales, Austrália. No entanto, no Brasil, estas plantas têm sido severamente prejudicadas pela ferrugem (Puccinia psidii Winter). Portanto, objetivamos estimar os parâmetros do sistema de reprodução e a herdabilidade para resistência a ferrugem em E. grandis por meio de um teste de progênies. Nós avaliamos a resistência a ferrugem em vinte e cinco progênies de polinização aberta, que foram severamente afetadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As N e is determined by the co-ancestry among individuals and inbreeding within individuals; and since without restriction some related individuals were selected, this resulted in a higher group of co-ancestry and lower N e than when selecting one tree per family. Maintenance of a high N e is important to avoid the loss of genetic diversity and allele fixation, which permits advancing genetic gain and is a buffer against stress (Lande and Barrowclough, 1987;Jurskis, 2005;Brawner et al, 2013;Bertoncini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As N e is determined by the co-ancestry among individuals and inbreeding within individuals; and since without restriction some related individuals were selected, this resulted in a higher group of co-ancestry and lower N e than when selecting one tree per family. Maintenance of a high N e is important to avoid the loss of genetic diversity and allele fixation, which permits advancing genetic gain and is a buffer against stress (Lande and Barrowclough, 1987;Jurskis, 2005;Brawner et al, 2013;Bertoncini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates also that some inbred individuals do not present inbreeding depression in the present population up to 3 years of age. Inbreeding has been observed in progeny trials of E. grandis open-pollinated seeds from two landraces in Brazil (Bertoncini et al, 2017), and in Eucalyptus globulus the effect of self-pollination was observed under field conditions months after planting (Hardner and Potts, 1994).…”
Section: Discussionmentioning
confidence: 99%